Health Safety and Environment Analysis in Food Manufacturing Installation Company to Eliminate Work Accidents - Zinedine Amrullah Sasmito; Tranggono (Future Science)
The manufacturing industry involving humans in carrying out the production process can involve a risk of work accidents, a combination of the possibility of a hazardous event, or the severity of an injury caused by the incident. PT. XYZ already has Figure 1. Research Flowchart HSE standards in carrying out this work, but work accidents can still occur due to various factors. According to statistics obtained, the non-compliance of employees with the rules of HSE (unsafe acts) and condition in the work area (hazardous condition) according to statistics received a value of 80% is caused by dangerous acts and 20% is caused by unsafe conditions. The research method used is descriptive analysis with data collection through observation and in-depth interviews with the HSE Site Officers and HSE Manager. Data retrieval is also added with specific data, which will then be concluded into general data. Data validity is done by collecting data from observations or interviews with various sources. Overall the implementation of HSE at PT. XYZ has been very good with fulfilling all aspects needed to help minimize the number of work accidents in the workplace.